Entrepreneurial Failure: A Synthesis and Conceptual Framework of its Effects. Issue 1 (25th August 2020) - Klimas, Patrycja; Czakon, Wojciech; Kraus, Sascha; Kailer, Norbert; Maalaoui, Adnane
Abstract : Failure is not the outcome which entrepreneurs strive for when they start their businesses. However, thousands of entrepreneurs fail each year, experiencing painful and damaging consequences in their professional and private lives. Current knowledge on entrepreneurial failure is quite fragmentary. Our study aims at integrating knowledge on the effects of entrepreneurial failure. Departing from a systematic literature review, we develop a multilevel framework of entrepreneurial failure effects which categorises: (1) their manifestations over time; (2) the directness of the link to the failure event; (3) the degree of impact on the failed entrepreneur; and (4) the level of long‐term outcomes generated. Our findings reveal a broad scope of multilevel impacts of entrepreneurial failure .